Penerapan Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange pada Materi Turunan Fungsi - Rika Handayani (Journal on Education, 2023)
This study aims to determine the learning outcomes through the RTE type cooperative learning model on Derivative Functions material and to determine student responses to the RTE type cooperative learning model. The approach used is a quantitative approach. The type of research is experimental research with a one-shot case study design. The population of all students of class XI SMA Negeri 3 Banda Aceh, the sample was taken randomly as much as 1 class, namely class XI IPA. Data collection techniques are carried out by carrying out learning outcomes tests. Data processing is done by testing the Run Test. The conclusion that can be drawn is that "student learning outcomes through the RTE type cooperative learning model have not been able to achieve a level of success in Derivative Function material in class XI SMA Negeri 3 Banda Aceh". As for the response, students gave a positive response to learning mathematics by using the RTE type cooperative model.